The Dictionary of Americanisms. A formal approximation to Spanish lexicon in America - Eva Bravo-García (RiCognizioni, 2015)
The ASALE Americanism’s Dictionary is a work of undeniable relevance in the field of current Spanish lexicography. This work represents an approach to its foundations inserted in traditional lexicography’s context. Departing from the question of what an americanism is, the keys of usefulness from this work are adressed towards the research on Spanish language varieties and on Spanish as a second language teaching practice.